Novel approaches in development of cell penetrating peptides - Shah, Vatsal R.; Shah, Yamini D.; Athalye, Mansi N. (Creative Pharma Assent, 2021)
Therapeutic cargos which are impermeable to the cell can be delivered by cell penetrating peptides (CPPs). CPP-cargo complexes accumulate by endocytosis inside the cells but they fail to reach the cytosolic space properly as they are often trapped in the endocytic organelles. Here the CPP mediated endosomal escape and some strategies used to increase endosomal escape of CPP-cargo conjugates are discussed with evidence. Potential benefits can be obtained by peptides such as reduction in side effects, biocompatibility, easier synthesis and can be obtained at lower administered doses. The particular peptide known as cell penetrating peptides are able to translocate themselves across membrane with the carrier drugs with different mechanisms. This is of prime importance in drug delivery systems as they have capability to cross physiological membranes. This review describes various mechanisms for effective drug delivery and associated challenges